If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5(3 + -2x) = 5 2x + (3 * -5 + -2x * -5) = 5 2x + (-15 + 10x) = 5 Reorder the terms: -15 + 2x + 10x = 5 Combine like terms: 2x + 10x = 12x -15 + 12x = 5 Solving -15 + 12x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 12x = 5 + 15 Combine like terms: -15 + 15 = 0 0 + 12x = 5 + 15 12x = 5 + 15 Combine like terms: 5 + 15 = 20 12x = 20 Divide each side by '12'. x = 1.666666667 Simplifying x = 1.666666667
| x(3x-2)+x(2x-7)=(5x+3)(x-6) | | -23b=20.7 | | 9y-4y-2y=5 | | y=-3x^2+3x+18 | | 3t-5t=6 | | 8d=4/5 | | 24/x=12/50 | | 6-5y=1 | | 97=-3+5(5-3x) | | (7-v)(3v-2)=0 | | (98x+61y)/1.84=80 | | 5a+6b=140 | | 2-2t-4x=2 | | 6p+7p=-13 | | 9+3j=22 | | 6y+3x=8 | | 6v=-13 | | 56-5h=34 | | 4(8x^2-5)-[6(4x^2-5)+3]= | | 156=3(6w-9) | | 12+6n=84 | | 4x-2[6-(7-4x)]= | | 3.2y-9-5y+4.8x=5.7x | | Xy+x=-3 | | 5(8y-6)-(7y+5)= | | 9x-5x-6x=7x | | 9(3y-9)-(2y+7)= | | 7x+2(x-2)=9x+12 | | w+(5/2)w=7.5 | | 12-7x=2x+20 | | 11y^2+3=36 | | 3xy-6xyz=3 |